Development and Evaluation of Vegetable Milk from Treculia africana (Decne) Seeds - Onweluzo, Jane C.; Nwakalor, Chizoba (Pakistan Journal of Nutrition, 2009)
Treculia africana seed milks (TRASMS) were developed using two blanching treatments (water and 0.2 % NaHCO3) and five seed to solvent ratios (1:1 to 1:5). The developed milks were subjected to consumer acceptance test. The lower solvent TRASMS were most acceptable. Sensory, physico-chemical and microbiological properties of the four most acceptable TRASMS were compared with soymilk and a commercial vegetable milk-vitamilk using standard analytical methods. Blanching in alkali overtly affected the colour and taste scores of TRASMS. Water blanched TRASMS were preferred by taste panelists in terms of flavour, taste, mouth feel and overall acceptability. Sensory scores of TRASMS differed significantly (P < 0.05) in all attributes from those of vitamilk. Blanching in alkali resulted in 6%-15% decrease in protein content, marginal (P > 0.05) increase in pH and significant (P < 0.05) increase in total solids in comparison to blanching in water. Ether extract was lower by (1.32%-1.81%) in all TRASMS than codex standard. The levels of Calcium in TRASMS was low but iron (0.40-0.52 mg/100ml) and vitamin C (3.38-3.46 mg/100ml) were appreciably high when compared with the levels in dairy and human milk. The microbial load of TRASMS was below the acceptable limit for dairy milk.